Evaluation of anti-gout potential of selected Malaysian medicinal plants - Abu Bakar, Fazleen Izzany (2020)
Gout is a type of arthritis that causes painful inflammation in joints due to the elevation of uric acid in the blood. Allopurinol is a common drug used for treating gout. However, due to unwanted side effects, new alternatives with fewer side effects are desired. The objectives of the study are to screen the six potential Malaysian medicinal plants for anti-gout activity using in vitro enzyme assay; to optimize the extraction conditions of the three selected plants using response surface methodology (RSM); to determine the cell viability of the three extracts towards RAW 264.7 murine macrophage cell line; to investigate the in vivo anti-gout mechanism of three selected plants; and to profile the bioactive compounds present in the three selected plant extracts. Six selected plants were screened for their anti-gout activity in vitro of which three plants (i.e Euphorbia hirta, Strobilanthes crispa and Christia vespertilionis) were further analyzed for their optimum extraction conditions using RSM. The effects of the plant extracts on the serum uric acid levels in hyperuricemic rats were then evaluated and lastly the bioactive compounds of the plant extracts were analyzed using liquid chromatography-mass spectrometry (LC-MS). E. hirta, S. crispa and C. vespertilionis exhibited XO inhibitory activity in vitro with more than 60 % at 100 µg/mL. Findings showed that the optimum extraction conditions of phytochemical compounds and anti-gout activity of these plants were at temperature of 65.09-79.07 °C for 5.0-17.42 min with solid to liquid ratio of 1:17.33-1:20 g/mL, respectively. C. vespertilionis displayed less cytotoxic against RAW264.7 cells as compared to S. crispa and E. hirta. For the in vivo study, the treatment of the hyperuricemic rats with 200 mg/kg of E. hirta, S. crispa and C. vespertilionis extracts reduced the serum uric acid levels significantly by more than 40 % as compared to hyperuricemic rats. The LC-MS analysis also revealed the presence of phytochemicals such as flavonoid and phenolic compounds in the plant extracts which might be associated with the anti-gout activity. Hence, this study clearly demonstrated that E. hirta, S. crispa and C. vespertilionis aqueous extracts are potential as anti-gout agents.